Compare the Outcomes of Laparotomy Versus Laparostomy Tube in Neonates Presented with Pneumoperitoneum - Gauri Shankar Pandit, Ranjana Kumari Pandit, Faisal Mahmood , Nahida Burki, Rija Nawaz Abbassi, Fatima Al Zahra, Asad Iqbal, Nadeem Akhtar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to compare the outcomes of laparotomy versuslaparostomy tube in neonates presented with pneumoperitoneum. Study Design: Retrospective study Place and Duration: Children Hospital, Pakistan Institute of Medical Sciences PIMS Islamabad. Jan 2021-Dec 2021 Methods: There were 130 neonates of both genders were presented in this study. All the included neonates had pneumoperitoneum and admitted for surgery of abdomen. Detailed demographics of enrolled cases were recorded after taking informed written consent. Patients were equally divided in two groups. Group A received laparotomy among 65 patients and group B received laparostomy tube (conservative management) among 65 patients. Outcomes among both groups were assessed and compared in terms of efficacy, hospital stay, complications and pain score by visual analog score. Results: Majority of the neonates were males 78 (60%) and 52 (40%) neonates were females. Most common symptom was abdominal and scrotal distension, followed by vomiting, cyanosis, respiratory distress and tachypnea.Efficacy of group B was found among 55 (84.6%) cases, 6 cases required laparotomy and 4 patients were died because of sepsis. Hospital stay was lower in group B 3.9±10.74 days as compared to group A 6.2±11.41 days. Post-operative lower pain score was observed in group B 0.9±1.66 as compared to group A 4.2± 2.53. Complications were also higher in group A found in 10 (15.4%) cases as compared to group B in 4 (6.2%) cases. Conclusion: We concluded in this study that use of laparostomy tube among neonates with pneumoperitoneum was equally affective and useful in terms of success rate while hospital stay, and complications were lower as compared to laparotomy group. Keywords: Pneumoperitoneum, Hospital stay, Laparotomy, Laparostomy tube, Complications, Pain Score